2020
DOI: 10.1192/bjo.2020.85
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric presentation of patients with acute SARS-CoV-2 infection: a retrospective review of 50 consecutive patients seen by a consultation-liaison psychiatry team

Abstract: Background Reports of psychiatric morbidity associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection tend to be limited by geography and patients’ clinical status. Representative samples are needed to inform service planning and research. Aims To describe the psychiatric morbidity associated with SARS-CoV-2 infection (confirmed by real-time polymerase chain reaction) in referrals to a consultation-liaison psychiatry service in Qatar. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 22 publications
5
50
2
4
Order By: Relevance
“…In this context, it can be said that it is no surprise that COVID-19 causes delirium. To our knowledge, in the only study evaluating psychiatric consultations in COVID-19 wards, Iqbal et al (2020) reported that delirium was 26% in a sample of 98% males with a mean age of 43.9. In our study, the rate of delirium diagnosis was higher in patients who requested a consultation (38.2%).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this context, it can be said that it is no surprise that COVID-19 causes delirium. To our knowledge, in the only study evaluating psychiatric consultations in COVID-19 wards, Iqbal et al (2020) reported that delirium was 26% in a sample of 98% males with a mean age of 43.9. In our study, the rate of delirium diagnosis was higher in patients who requested a consultation (38.2%).…”
Section: Discussionmentioning
confidence: 86%
“…In general, it can be said that the reasons for requesting consultations in the present study (although the frequency and order varied) did not differ from the results of previous studies of patients in general hospital wards ( Göktaş et al, 2006 ; Wilson et al, 2012 ; Eser et al, 2018 ). However, a small number of studies conducted with patients with COVID-19 found that these complaints were more common in patients after psychiatric evaluations ( Helms et al, 2020 ; Iqbal et al, 2020 ). In a recent study investigating psychiatric morbidity in patients with COVID-19 ( Iqbal et al, 2020 ) who were referred to the consultation-liaison psychiatry service, it was reported that the most common symptoms of patients were insomnia (70%), anxiety (64%), agitation (50%) and depressive mood (42%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 There is accumulating evidence of higher rates of symptoms of common mental health problems such as anxiety and insomnia 2 , 3 , 4 associated with the current pandemic, with some reports of severe psychiatric disorders including mania and psychosis. 5 , 6 , 7 These may arise directly from the effects of infection with enforced isolation and quarantine after viral exposure, or indirectly from additional stressors such as complicated bereavement, job losses, intra-familial tension and sudden impoverishment. So how may a psychiatrist make a useful contribution, both in the midst and aftermath of a viral pandemic?…”
Section: Introductionmentioning
confidence: 99%
“…Depression has led the number of publications related to these conditions but stress also is a matter of great concern. [4][5][6][7] According to Selye 8 stress is abstract; it does not exist in a pure state and, like life, is very difficult to define. Stress on a rat or a man does not exist as such; it appears to be combined with something, that is, it depends on a specific agent to be produced.…”
Section: Introductionmentioning
confidence: 99%